Factors Influencing Students’ Well-being on Educational Outcomes in the Indonesian Railway Polytechnic - Ainun Fikria; Akhyat Hilmi; Afita Prastiwi (Department of English Language Education, UIN Sunan Ampel Surabaya, 2021)
Students’ well-being among Indonesian scholars might be still unpopular as this topic could lead to a blundered result in a certain area of disciplines. Yet, this topic is essential to reveal as it can be one of the indicators which can be taken into account on measuring the workload of students enrolling in this state-owned institution. Not only that, but this also might be an eminent output indicator for the quality of education specifically on educational outcomes. The instruments occupied in this study were interviews and surveys. Students and alumni of the polytechnic were asked to participate in this study and several key figures as well. This study applied a mixed-method research design, which is commonly accepted as there are both qualitative and quantitative parts combined in the study. The results showed that the quality of student well-being in an emotional, social, and school dimension of student PPIM is relatively at a good level. Hence, with the tight schedule and tough physical activity, the institution should pay attention to a psychological aspect.